P224 Anti-PARP1 as a novel autoantibody in myositis. (23rd April 2022) - Riddell, Victoria; Betteridge, Zoe; Bowler, Elizabeth; Chinoy, Hector; Gordon, Patrick; Wedderburn, Lucy; Bagby, Stefan; Mchugh, Neil; Tansley, Sarah
Abstract: Background/Aims: Idiopathic inflammatory myopathies (IIM) are multisystem diseases characterised by muscle inflammation. Over 60% of patients with IIM have a myositis-related autoantibody. Our laboratory specialises in autoantibody testing. We offer an extended spectrum autoantibody testing diagnostic service and have also screened over 3000 myositis patients enrolled in research studies for the presence of autoantibodies. We noticed a recurring pattern following K562 cell radio-immunoprecipitation that was present in several myositis patient sera and in a handful of samples that came to us via the diagnostic service. We set out to determine the antigenic target of this novel autoantibody. Methods: We have previously screened 1319 serum/plasma samples from IIM patients enrolled in the UKMyoNet and 380 from patients with juvenile onset IIM enrolled in the JDCBS for autoantibodies by immunoprecipitation. Additional cohorts similarly investigated include >150 healthy control sera and >400 SLE patient sera. Patients with the novel autoantibody of interest were identified by a distinctive 120kDa band associated with a 'smear' on autoradiography following K562 cell immunoprecipitation and separation of autoantigens by SDS PAGE. ESI-QTOF mass spectrometry was used to identify the antigenic target in an example serum. Using a commercial anti-PARP1 antibody as a control, western blotting of K562 and PARP1 overexpressed cell lysate was used to confirm the antigenic target in remaining samples of interest. Indirect immunofluorescence was performed on HEp-2 cells according to manufacturers' instructions. Results: 11 patient samples were identified as having the 120 complex 'smear' pattern of interest: six had been received via the diagnostic service and five were enrolled in UKMyoNet. Prevalence in the UKMyoNet cohort was 0.4%. Mass spectrometry identified PARP1 as the antigenic target. This was confirmed in all remaining samples by western blot. Table 1 shows available clinical data. Conclusion: PARP1 is an autoantigen target in myositis patients in addition to those with other rheumatic diseases. Where data was available, patients with anti-PARP1 had features suggesting an anti-synthetase syndrome phenotype, but this may primarily relate to the other autoantibodies present. Further work is needed to determine the prevalence of anti-PARP1 in other cohorts and its clinical associations. Disclosure: V. Riddell: Grants/research support; Bath Institute of Rheumatic Disease. Z. Betteridge: None. E. Bowler: None. H. Chinoy: None. P. Gordon: None. L. Wedderburn: None. S. Bagby: None. N. Mchugh: None. S. Tansley: None.